Implementation of Service Quality in Order to Increase Patient Satisfaction of Simolawang Surabaya Health Center - Arie Ferdiana (International Journal of Social, Economic, and Business, 2025)
This study aims to evaluate the implementation of service quality in improving patient satisfaction at UPT Puskesmas Simolawang, Surabaya. Using a descriptive quantitative approach, data were collected from 182 patients through structured questionnaires based on the SERVQUAL model, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Descriptive statistical analysis was used to assess public perceptions of service performance in each dimension. The results show that the overall service quality is perceived as “very good,” with the assurance dimension receiving the highest score, particularly on the item related to the availability of free healthcare services. Conversely, the responsiveness dimension received the lowest score, especially on the item concerning the timeliness of staff response during peak hours. These findings suggest that while trust, professionalism, and equitable access are strengths of the institution, improvements in real-time service responsiveness and infrastructure comfort are needed. The study contributes to the ongoing discourse on quality improvement in primary healthcare and provides practical recommendations for public health administrators to enhance patient-centered services using the SERVQUAL framework.